OTU-021 Effect of the two-week wait referral pathway on colorectal cancer detection: systematic review and meta-analysis. (8th June 2018) - Mozdiak, Ella; Weldeselassie, Yonas; McFarlane, Michael; Tabuso, Maria; Widlak, Monika; Dunlop, Amber; Arasaradnam, Ramesh
Abstract : Introduction: In 2000 the two-week-wait (TWW) suspected cancer pathway was launched; national TWW performance data is lacking. This systematic review is the first to comprehensively evaluate the latest evidence on cancer detection through the TWW for suspected lower gastrointestinal malignancy. Method: This systematic review is reported according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses [PRISMA] 2009 statement. Cochrane, EMBASE, Medline via Pubmed, NHS Evidence, Trip and the British Library Catalogue were searched, plus references were hand-searched. Disagreements were resolved via consensus. Meta-analysis of pooled cancer conversions rates with 95% confidence intervals were calculated using a random effects model in R studio. Results: 95 full papers and 28 conference abstracts were reviewed. 77.5% full papers reported cancer conversion rate, corresponding weighted mean was calculated with a cancer conversion rate of 7.7% (6.9–8.5 C.I). A forest plot of full-text paper results is shown in figure 1. Conclusion: The pooled cancer conversion rate via TWW is similar to the cancer detection rate in the asymptomatic Bowel Cancer Screening Population (latest figure 8%) and is not having its intended impact on cancer diagnosis. Re-evaluation of the referral criteria needs consideration, focusing on symptoms with higher PPV in cancer.